Polystyrene nanoparticle-templated hollow titania nanosphere monolayers as ordered scaffolds. Issue 10 (21st February 2018) - Robbiano, V.; Paternò, G. M.; Cotella, G. F.; Fiore, T.; Dianetti, M.; Scopelliti, M.; Brunetti, F.; Pignataro, B.; Cacialli, F.
Abstract : A novel class of ordered mesoporous titania scaffolds prepared via colloidal lithography is attractive for perovskite-based solar cells thanks to the increased light-trapping inside the perovskite layer induced by the feedback structure and to the improved perovskite film. Abstract : We report a novel multi-step method for the preparation of ordered mesoporous titania scaffolds and show an illustrative example of their application to solar cells. The method is based on (monolayer) colloidal nanosphere lithography that makes use of polystyrene nanoparticles organised at a water–air interface and subsequently transferred onto a solid substrate. A titania precursor solution (titanium(iv ) isopropoxide in ethanol) is then drop-cast onto the monolayer and left to "incubate" overnight. Surprisingly, instead of the expected inverse monolayer-structure, a subsequent calcination step of the precursor yields an ordered monolayer of hollow titania nanospheres with a wall thickness of ∼30–50 nm, and a slightly larger diameter than that of the starting spheres. X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) characterization of such scaffolds confirm that they consist of nanocrystalline anatase titania, and that any polystyrene/carbon residues in the scaffolds are below the XPS detection level. As an illustrative application we prepared perovskite solar cells incorporating the templated-nanoparticle scaffolds displaying a respectable power conversion efficiency of ∼9%, twice as large as that of our unoptimized "reference" cells ( i.e. incorporating conventional mesoporous or compact titania scaffolds), thereby also demonstrating that the process is relatively robust with respect to optimization of the process parameters.